Pengaruh pembelajaran pencak silat terhadap peningkatan keterampilan motorik dan pembentukan karakter siswa SD - Fahrizal, Fahrizal; Hudain, Muh. Adnan; Jalil, Rasyidah (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Pencak silat is one of the martial arts that needs to be taught from an early age, especially to elementary school students. This study aims to determine the effect of pencak silat learning on improving students' motor skills and character. It will use a quasi-experimental research method with a one-group pretest-posttest design. Samples were taken using purposive sampling with the criteria of children aged 10-12 years and routinely participating in training for 12 weeks, totaling 20 students. Data collection techniques used sit ups, V sit and reach, stork stand, and questionnaires to measure student character. The instrument was valid with a reliability value of 0.92. The data analysis technique used an independent sample t-test with the help of the SPSS 29 program, which compared the mean between the pretest and posttest results. The results found that before pencak silat learning, students' motor skills were dominantly in the moderate category. After applying pencak silat learning, the dominant motor skills are in a good category with a P-value for the motor component of 0.004 <0.05, indicating a significant difference between the motor component before and after participating in pencak silat learning. Likewise, the character value of students also experienced a significant increase after pencak silat learning with a P-value of 0.002 <0.05, which indicates that there is a significant difference between character values before and after participating in pencak silat learning.